Local taxes and fees as a source of revenue for polish municipalities: Substitutes or complements? - Julita Łukomska; Jarosław Neneman (e-Finanse: Financial Internet Quarterly, 2018)
The main purpose of this article is analysis of the relationship between local tax and fee policies in Poland. We argue that local authorities have similar and significant discretion over tax and fee policy and, therefore, they can be analysed in a similar way. Links between these policies are analysed to find out whether they are of complementary or substitutive nature. Panel data on 578 Polish municipalities from 2012 to 2016 includes information on property tax rates and tariffs for water provision and sewage disposal for households and companies and is used to run panel regression analysis and to perform a quasi-experiment. The results indicate that there is a relationship between tax and fee policies as well as that taxes and fees are complements for local authorities. Only when a property tax rate has reached a 'ceiling', the municipalities increase fees at a faster rate than comparable municipalities below the ceiling - in this case a fee can be regarded as a substitute for a tax. The paper is based on results of the 'Fees for local public services - financial and political importance' research project. The project is funded by Narodowe Centrum Nauki (National Science Centre) grant number UMO-2015/19/B/HS4/02898.
Keywords: H71; H76; H79; 330; local government; public finance; tax policy; political economy of taxes and fees; charges for local services; Poland